Many, but not all, outcome studies support exclusion of female plasma from the blood supply. Issue 5 (October 2010) - Stafford-Smith, Mark; Lockhart, Evelyn; Bandarenko, Nicholas; Welsby, Ian
Transfusion-related acute lung injury (TRALI) has been identified as the most common cause of transfusion-related death. Although extensive literature supports restrictions on female-donor plasma to reduce antibody-mediated TRALI, only a few outcome studies have assessed for effects of this change, and some, but not all, have endorsed the policy. A recent report even suggests poorer outcomes in cardiac surgery patients with a shift to male-donor-only plasma, raising concerns that TRALI alone, whether catastrophic or more survivable, is insufficient compared with broader measures, such as short-term mortality or long-term survival, as an end point to assess for overall improvements in patient care.